In The Taratory. - In The Taratory (Canberra : In The Taratory, 2011)
"Welcome to In The Taratory! I'm T1*, a mid-20s Queenslander who moved to Canberra for work just over five years ago (am almost a local!). I know there can be a bit of bad press both outside this fair capital and within (Canberrans are often their own worst enemy!) about lack of things to do, and am passionate about proving this wrong. I'm regularly getting out there finding and experiencing all the things to do in Canberra and surrounds, and am willing to give most anything a go ... "--About In The Taratory
Title from title screen (viewed on 6 February 2014)
Mode of access: Available online. Address as at 2/6/14
Selected for archiving
Keywords: Blogs -- Australian Capital Territory -- Canberra; Australian